2014
DOI: 10.1007/s00167-014-3298-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tensiomyographic neuromuscular characteristics between muscles of the dominant and non-dominant lower extremity in male soccer players

Abstract: Prognostic study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 26 publications
(109 reference statements)
4
32
2
4
Order By: Relevance
“…The results obtained in the conducted research coincide with the majority of the results from the previous studies conducted on a sample of international football players (Alvarez-Diaz et al, 2014;García-García, Serrano-Gómez, & Cuba-Dorado, 2014;García-García, Serrano-Gómez, Hernández-Mendo, & Morales-Sánchez, 2017;Gil et al, 2015) in which the authors have also concluded that there are no statistically significant differences in the measured TMG variables BF of the Dom and NonDom leg. Also, very similar descriptive results of the examined variables were obtained on a sample of futsal (Sánchez-Sánchez et al, 2018), volleyball players (Rodríguez-Ruiz et al, 2012) and cyclists (García-García et al, 2013) in regard to the studied BF muscle.…”
Section: Discussionsupporting
confidence: 88%
“…The results obtained in the conducted research coincide with the majority of the results from the previous studies conducted on a sample of international football players (Alvarez-Diaz et al, 2014;García-García, Serrano-Gómez, & Cuba-Dorado, 2014;García-García, Serrano-Gómez, Hernández-Mendo, & Morales-Sánchez, 2017;Gil et al, 2015) in which the authors have also concluded that there are no statistically significant differences in the measured TMG variables BF of the Dom and NonDom leg. Also, very similar descriptive results of the examined variables were obtained on a sample of futsal (Sánchez-Sánchez et al, 2018), volleyball players (Rodríguez-Ruiz et al, 2012) and cyclists (García-García et al, 2013) in regard to the studied BF muscle.…”
Section: Discussionsupporting
confidence: 88%
“…Тензиомиографија је учестало примењивана и у спорту и то код фуд-балера (Rey, Lago-Peñas, & Lago-Ballesteros, 2012;Rusu et al, 2013;Alvarez-Diaz et al, 2014), одбој-каша (Rodriguez-Ruiz et al, 2014Dopsaj, Ivanovic, & Ćopić, 2014), триатлонаца (Garcia-Manso et al, 2011), бициклиста (García-García, Cancela-Carral, Martínez-Trigo, & Serrano-Gómez, 2013), кајака-шица (García-García, Cancela-Carral, & Huelin--Trillo, 2015 као и код професионалних плесача (Zagorc, Šimunič, Pišot, & Oreb, 2010).…”
Section: уводunclassified
“…Можемо претпоставити да мишићи ВЛ и ВМ имају највећи проценат брзих мишићних влакана као и да су мање подложни неуромишићном замору. Када се резултати овог истраживања упореде са резултатима претходних сличних студија може се закључити да се време латентне реакције мерених мишића (Td) нала-зи у распону података у односу на утрениране и неутрениране појединце (Zagorc et al, 2010;Pišot et al, 2010;Tous-Fajardo et al, 2010; Garcia-Manso et al, 2011;Šimunič, 2012;Alvarez-Diaz et al, 2014;Loturco et al, 2015).…”
Section: дискусијаunclassified
See 2 more Smart Citations